Adverse metabolic and mental health outcomes associated with shiftwork in a population-based study of 277, 168 workers in UK biobank*. (4th July 2017) - Wyse, Cathy A.; Celis Morales, Carlos A.; Graham, Nicolas; Fan, Yu; Ward, Joey; Curtis, Anne M.; Mackay, Daniel; Smith, Daniel J.; Bailey, Mark E. S.; Biello, Stephany; Gill, Jason M. R.; Pell, Jill P.
Abstract: Background: Reported associations between shiftwork and health have largely been based on occupation-specific, or single sex studies that might not be generalizable to the entire working population. The objective of this study was to investigate whether shiftwork was independently associated with obesity, diabetes, poor sleep, and well-being in a large, UK general population cohort. Methods: Participants of the UK Biobank study who were employed at the time of assessment were included. Exposure variables were self-reported shiftwork (any shiftwork and night shiftwork); and outcomes were objectively measured obesity, inflammation and physical activity and self-reported lifestyle, sleep and well-being variables, including mental health. Results: Shiftwork was reported by 17% of the 277, 168 employed participants. Shiftworkers were more likely to be male, socioeconomically deprived and smokers, and to have higher levels of physical activity. Univariately, and following adjustment for lifestyle and work-related confounders, shiftworkers were more likely to be obese, depressed, to report disturbed sleep, and to have neurotic traits. Conclusions: Shiftwork was independently associated with multiple indicators of poor health and wellbeing, despite higher physical activity, and even in shiftworkers that did not work nights. Shiftwork is an emerging social factor that contributes to disease in the urban environment across the working population. Key messages: Studies have linked shiftwork to obesity and diabetes in nurses and industry workers, but little is known about the implications of shiftwork for the general workforce In this large cross sectional study of UK workers, shiftwork was associated with obesity, depression and sleep disturbance, despite higher levels of physical activity. Shiftwork was associated with multiple indicators of compromised health and wellbeing and were more likely to report neurotic traits and evening preference